FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN EKONOMI RUMAHTANGGA PETANI KAKAO DI KABUPATEN KUANTAN SINGINGI - Nurhayati '; Djaimi Bakce; Yusmini ' (Indonesian Journal of Agricultural Economics, 2012)
The present research was aimed to analyze internal and external factors which affect theallocation of working time, household income and expenditure of cocoa farmers inKuantan Singingi Regency and investigated the impact of economic change with respectto the development of cocoa farming on the economic decision making of the farmershousehold. In general, the results show that there were no internal factors such asproduction, the allocation of working time and income, which responsively affected thecocoa farm household economy. However, from their expenditure there was aresponsive internal factor which affected their total income, education and lifeexpectancy. There was a positive effect of the effort made by the cocoa farmer family toincrease the price of the dried and wet cocoa beans on their household economy. Incontrast, increased wages had a negative effect on the household economy of thefarmers.Keywords: internal and external factors, household economic decision, cocoa.